ISU-ISU EKONOMI ISLAM DAN PENGIMPLEMENTASIANNYA DALAM KEMASLAHATAN UMAT - Yani, Misri; Syahriza, Rahmi; Tarigan, Azhari Akmal (AGHNIYA : Jurnal Ekonomi Islam, 2024)
This study examines thematic interpretations and hadiths related to things that are prohibited in Islam from the perspective of Islamic economics. Islam as a comprehensive religion regulates various aspects of life, including economics. In this context, the study aims to explore the teachings contained in the Qur'an and Hadith regarding prohibitions related to economic activities, such as usury, fraud, monopoly, and injustice in transactions. The method used is the thematic interpretation approach (maudhu'i) to interpret relevant verses of the Qur'an and analysis of hadiths related to the principles of Islamic economics.. The results of the study show that these prohibitions are not only intended to maintain social and moral balance, but also to encourage the creation of an economic system based on justice, transparency, and the welfare of the people. The implications of this study provide important insights for the application of Islamic economic principles in everyday life and the development of more equitable economic policies.